The Role of National Drug Law Enforcement Agency (NDLEA) in Mitigating Drug Abuse Among Youths in Kogi State - Alhaji Zekeri Obaje (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
The study assesses the role of National Drug Law Enforcement Agency (NDLEA) in mitigating drug abuse among youths in kogi state. Plethora of reports abound from national surveys and law-enforcement agencies that there is a persistent rise in the use of substances such as cannabis, tramadol, codeine-based cough syrups, and other psychoactive drugs among young people, leading to increased incidences of crime, school dropout, health complications, and social disintegration. Thus, the study assesses the pattern of drug abuse among youths, evaluate the effects of NDLEA’s awareness creation programme on drug abuse among youths, ascertain the effects of NDLEA’s law enforcement strategies in reducing drug trafficking and abuse among the youths in Kogi State and identify the challenges militating against the activities of NDLEA in the bid to fulfil her mandate. Proneness theory was adopted as the theoretical framework for the study. The research design for this study was descriptive survey research design. The total population of the study was 438,364 and a sample size of 384 was drawn using the Krejcie and Morgan’s sample size determination table. The study revealed that drug abuse among youths is dominated by marijuana, tramadol, and codeine or non-codeine cough syrups. Also, the study revealed that a significant majority of respondents perceived NDLEA’s awareness creation programmes as effective in reducing drug abuse. In addition, the study found that there is a significant relationship between NDLEA strategies and drug abuse prevalence, indicating that increased NDLEA enforcement activities are associated with reduced drug abuse among youths. Equally, the study found that inadequate funding, lack of comprehensive rehabilitation centres, limited community support, and the activities of sophisticated drug cartels constitute major challenges confronting NDLEA in the state. Amongst others, the study recommends that Government and relevant stakeholders should intensify targeted interventions focusing specifically on marijuana, tramadol, and codeine misuse, as these are the dominant substances among youths. Also, NDLEA should expand and sustain its awareness campaigns through continuous school-based education, social media engagement, radio and television programmes, and youth-centered community outreach. Furthermore, NDLEA should strengthen inter-agency collaboration with the police, customs, and other security agencies to enhance intelligence sharing and coordinated enforcement. Finally, government should increase funding allocation to NDLEA to improve logistics, manpower, operational capacity, and infrastructure for enhanced performance.